MALDI mass spectrometry reveals that cumulus cells modulate the lipid profile of in vitro-matured bovine oocytes. (4th March 2017) - Vireque, Alessandra A.; Tata, Alessandra; Belaz, Katia Roberta A.; Grázia, João Gabriel V.; Santos, Fábio N.; Arnold, Daniel R.; Basso, Andrea C.; Eberlin, Marcos N.; Silva-de-Sá, Marcos Felipe; Ferriani, Rui A.; Sá Rosa-e-Silva, Ana Carolina J.
ABSTRACT: The influence of cumulus cells (CC) on the lipid profile of bovine oocytes matured in two different lipid sources was investigated. Cumulus-oocyte complexes (COC) or denuded oocytes (DO) were matured in tissue culture medium (TCM) supplemented with fetal bovine serum (FBS) or serum substitute supplement (SSS). Lipid profiles of TCM, serum supplements, immature CC and oocyte (IO), and in vitro -matured oocytes from COC and DO were then analyzed by matrix assisted laser desorption ionization mass spectrometry (MALDI-MS) and submitted to partial least squares-discriminant analysis (PLS-DA). The developmental competence of such oocytes was also assessed. Differences in lipid composition were observed between two types of sera and distinctly influenced the lipid profile of CC. As revealed by PLS-DA, the abundance of specific ions corresponding to triacylglycerols (TAG) or phospholipids (PL) were higher in COC compared to DO both supplemented with FBS or SSS and to some extent affected the subsequent DO in vitro embryo development. DO exposed to SSS had however a marked diminished ability to develop to the blastocyst stage. These results indicate a modulation by CC of the oocyte TAG and PL profiles associated with a specific cell response to the serum supplement used for in vitro maturation.